Human Primary Epithelial Cells Acquire an Epithelial-Mesenchymal-Transition Phenotype during Long-Term Infection by the Oral Opportunistic Pathogen, Porphyromonas gingivalis - Lee, Jungnam; Roberts, JoAnn S.; Atanasova, Kalina R.; Chowdhury, Nityananda; Han, Kyudong; Yilmaz, Özlem (Frontiers in Cellular and Infection Microbiology, 2017)
Porphyromonas gingivalis is a host-adapted oral pathogen associated with chronic periodontitis that successfully survives and persists in the oral epithelium. Recent studies have positively correlated periodontitis with increased risk and severity of oral squamous cell carcinoma (OSCC). Intriguingly, the presence of P. gingivalis enhances tumorigenic properties independently of periodontitis and has therefore been proposed as a potential etiological agent for OSCC. However, the initial host molecular changes induced by P. gingivalis infection which promote predisposition to cancerous transformation through EMT (epithelial-mesenchymal-transition), has never been studied in human primary cells which more closely mimic the physiological state of cells in vivo. In this study, we examine for the first time in primary oral epithelial cells (OECs) the expression and activation of key EMT mediators during long-term P. gingivalis infection in vitro. We examined the inactive phosphorylated state of glycogen synthase kinase-3 beta (p-GSK3β) over 120 h P. gingivalis infection and found p-GSK3β, an important EMT regulator, significantly increases over the course of infection (p < 0.01). Furthermore, we examined the expression of EMT-associated transcription factors, Slug, Snail, and Zeb1 and found significant increases (p < 0.01) over long-term P. gingivalis infection in protein and mRNA expression. Additionally, the protein expression of mesenchymal intermediate filament, Vimentin, was substantially increased over 120 h of P. gingivalis infection. Analysis of adhesion molecule E-cadherin showed a significant decrease (p < 0.05) in expression and a loss of membrane localization along with β-catenin in OECs. Matrix metalloproteinases (MMPs) 2, 7, and 9 are all markedly increased with long-term P. gingivalis infection. Finally, migration of P. gingivalis infected cells was evaluated using scratch assay in which primary OEC monolayers were wounded and treated with proliferation inhibitor, Mitomycin C. The cellular movement was determined by microscopy. Results displayed P. gingivalis infection promoted cell migration which was slightly enhanced by co-infection with Fusobacterium nucleatum, another oral opportunistic pathogen. Therefore, this study demonstrates human primary OECs acquire initial molecular/cellular changes that are consistent with EMT induction during long-term infection by P. gingivalis and provides a critically novel framework for future mechanistic studies.